Ellagic Acid Reduces Adipogenesis through Inhibition of Differentiation-Prevention of the Induction of Rb Phosphorylation in 3T3-L1 Adipocytes. (4th November 2013) - Wang, Lifeng; Li, Linlin; Ran, Xinjian; Long, Mei; Zhang, Minfang; Tao, Yicun; Luo, Xin; Wang, Ye; Ma, Xiaoli; Halmurati, Upur; Mao, Xinmin; Ren, Jun
Abstract : Ellagic acid (EA) present in many fruits and nuts serves as antiproliferation, anti-inflammatory, and antitumorigenic properties. However, the effect of EA on preadipocytes adipogenesis and its mechanism(s) have not been elucidated. The present study was designed to examine the effect of EA on adipogenesis in 3T3-L1 preadipocytes and underlying mechanism(s) of action involved. Data show that EA administration decreased the accumulation of lipid droplets. The inhibition was diminished when the addition of EA was delayed to days 2–4 of differentiation. Clonal expansion was reduced in the presence of EA. FACS analysis showed that EA blocked the cell cycle at the G1/S transition. EdU incorporation also confirmed that EA refrained cell from entering S phase. Our data also revealed that the differentiation-induced protein expression of Cyclin A and phosphorylation of the retinoblastoma protein (Rb) were impaired by EA. Differentiation-dependent expression and DNA-binding ability of C/EBP α were also inhibited by EA. Alterations in cell cycle-associated proteins may be important with respect to the antiadipogenic action of EA. In conclusion, EA is capable of inhibiting adipogenesis in 3T3-L1 adipocytes possibly through reduction of Cyclin A protein expression and Rb phosphorylation. With the blocking of G1/S phase transition, EA suppresses terminal differentiation and lipid accumulation in 3T3-L1 adipocytes.